Well-Possednes of a predator-prey reaction-diffusion model with functional response dependent on species - Pino-Romero, Neisser (2024)
In this work, the well-possednes of a predator-prey model with reaction-diffusion will be studied where the Allee effect in prey reproduction will be included and predation dynamics will be considered a functional response dependent on the species (prey and predator) with the incorporation of the refuge in the dam. In this way, the existence, uniqueness and positivity of the system's solutions as the main result will be guaranteed.